Are Wealthier People Healthier? An Analysis to Indonesian Baby Boomers - Setyanti, Axellina Muara; Wicesa, Nayaka Artha (Jurnal Ekonomi Kuantitatif Terapan, 2021)
The elderly population in Indonesia has doubled in the last five decades, along with an increase in life expectancy and mortality. Those who were born in the 1940s to 1960s or the baby boomer generation are those who are in old age now. There are many studies that analyze the relationship of wealth to one's health level, but not many have looked specifically at the elderly population. The objective of this study is to determine the effect of wealth on elderly’s health condition. Using binomial logistic regression, this study found that the highest average health probability of the elderly was 78.96 percent, i.e. those with working status, above average income and no expenditure on unhealthy commodities such as cigarettes, while the average health probability the lowest was 52.44 percent, i.e. those with non-work status, below-average income, and having expenditures for unhealthy commodities. This study found that wealth affects the health level of the elderly. These conclusions, accompanied by aging conditions in a country have policy implications that must consistently implement efforts to improve social welfare for the elderly, thereby creating healthy and active aging.